Prevalence of Latent Tuberculosis Infection Among Non-US-Born Persons by Country of Birth—United States, 2012–2017. (2nd November 2020) - Collins, Jeffrey M; Stout, Jason E; Ayers, Tracy; Hill, Andrew N; Katz, Dolly J; Ho, Christine S; Blumberg, Henry M; Winglee, Kathryn; ,
Abstract: Background: Most tuberculosis (TB) disease in the United States (US) is attributed to reactivation of remotely acquired latent TB infection (LTBI) in non-US-born persons who were likely infected with Mycobacterium tuberculosis in their countries of birth. Information on LTBI prevalence by country of birth could help guide local providers and health departments to scale up the LTBI screening and preventive treatment needed to advance progress toward TB elimination. Methods: A total of 13 805 non-US-born persons at high risk of TB infection or progression to TB disease were screened for LTBI at 16 clinical sites located across the United States with a tuberculin skin test, QuantiFERON Gold In-Tube test, and T-SPOT.TB test. Bayesian latent class analysis was applied to test results to estimate LTBI prevalence and associated credible intervals (CrIs) for each country or world region of birth. Results: Among the study population, the estimated LTBI prevalence was 31% (95% CrI, 26%–35%). Country-of-birth-level LTBI prevalence estimates were highest for persons born in Haiti, Peru, Somalia, Ethiopia, Vietnam, and Bhutan, ranging from 42% to 55%. LTBI prevalence estimates were lowest for persons born in Colombia, Malaysia, and Thailand, ranging from 8% to 13%. Conclusions: LTBI prevalence in persons born outside the US varies widely by country. These estimates can help target community outreach efforts to the highest-risk groups. Abstract : We estimated latent tuberculosis infection (LTBI) prevalence by birth country/region for 13 805 non-US-born persons in the United States. LTBI varies widely by nativity; providers and public health programs can use this information to prioritize populations for testing.